Timing Characterization of a Tester Operated Integrated Circuit by Continuous and Pulsed Laser Stimulation - Kiyan, Tuba; Brillert, Christof; Boit, Christian (ASM INTERNATIONAL, 2010)
The scope of this work is to investigate the timing characteristics of a state of the art fully functional IC through continuous wave (CW) and pulsed laser stimulation. The propagation delay of a gate depends on the drain current of nMOS and pMOS transistors, load capacitance and supply voltage. Localized photocurrent induced by laser beam alters some of these electrical characteristics, resulting in a change in the switching time of the gate. In addition to the desired local timing influence, a global effect on the timing throughout the full scanning period occurs as secondary phenomenon that - if not taken into account properly, may mask the local signal. This effect is strong under CW laser operation and can be drastically reduced in pulsed laser condition.
Keywords: Materials Science